Steelband Movement Marks 30 Years of Panorama - Tarradath, Selwyn (Trinidad Guardian)
This article discusses the 30th year Anniversary of the Panorama competition. In 1963, the National Association of Trinidad and Tobago Steelbandsmen took a decision to host a national steelband competition as part of the Dimanche Gras show.
Keywords: Steel bands (Music) -- Competitions -- Trinidad and Tobago; Panorama (Musical festival); Steel band music -- Trinidad and Tobago